THE EFFECT OF BRAND IMAGE AND BRAND TRUST ON BRAND LOYALTY IN PERSIB BANDUNG FOOTBALL CLUB - Puspita Yustina Putri Balaw; Marcellia Susan (Faculty of Economic and Business, University of Pasundan, 2022)
Indonesia has so many football clubs under PSSI, one of which is Persib Bandung from Bandung City. A top club that has many supporters in Indonesia. The good image attached to the club adds to the level of trust which will also affect loyalty to the club. This study was conducted to determine the effect of brand image and brand trust on brand loyalty, and whether brand trust is able to mediate. The method used is descriptive and causal method with a quantitative approach. The sample of this study amounted to 143 respondents, all of whom were members of the Viking Persib Club, with the technique used was non-probability sampling. Data was collected by distributing online questionnaires with google form, and the data analysus technique used was structural equation modeling (SEM). This study shows that brand image has a positive influence on brand loyalty and brand trust is able to mediate the effect of brand image on brand loyalty of Viking Persib Club at Persib Bandung.